New method for Earth neutral atmospheric density retrieval based on energy spectrum fitting during occultation with LE/Insight-HXMT. Issue 9 (1st May 2022) - Yu, Daochun; Li, Haitao; Li, Baoquan; Ge, Mingyu; Tuo, Youli; Li, Xiaobo; Xue, Wangchen; Liu, Yaning
Abstract: We propose a new method for retrieving the atmospheric number density profile in the lower thermosphere, based on the X-ray Earth occultation of the Crab Nebula with the Hard X-ray Modulation Telescope ( Insight -HXMT) Satellite. The absorption and scattering of X-rays by the atmosphere result in changes in the X-ray energy, and the Earth's neutral atmospheric number density can be directly retrieved by fitting the observed spectrum and spectrum model at different altitude ranges during the occultation process. The pointing observations from LE/ Insight -HXMT on 16 November 2017 are analyzed to obtain high-level data products such as lightcurve, energy spectrum and detector response matrix. The results show that the retrieved results based on the spectrum fitting in the altitude range of 90–200 km are significantly lower than the atmospheric density obtained by the NRLMSISE-00 model, especially in the altitude range of 110–120 km, where the retrieved results are 34.4% lower than the model values. The atmospheric density retrieved by the new method is qualitatively consistent with previous independent X-ray occultation results (Determan et al., 2007; Katsuda et al., 2021), which are also lower than empirical model predictions. In addition, the accuracy of atmospheric density retrieved results decreases with the increase of altitude in the altitude range of 150–200 km, and the accurate quantitative description will be further analyzed after analyzing a large number of X-ray occultation data in the future.